2016
DOI: 10.1161/hypertensionaha.116.07775
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cardiovascular Risk Factors on Graft Outcome Disparities in Black Kidney Transplant Recipients

Abstract: Although outcome inequalities for non-Hispanic Black (NHB) kidney transplant recipients are well documented, there is paucity in data assessing the impact of cardiovascular disease (CVD) risk factors on this disparity in kidney transplantation. This was a longitudinal study of a national cohort of veteran kidney recipients transplanted between Jan 2001 and Dec 2007. Data included baseline characteristics acquired through the USRDS linked to detailed clinical follow up information acquired through the VA electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…In a more recent analysis using national data, our research group demonstrated that posttransplant BP control (<140/90 mmHg) was significantly less common in AAs as compared with non‐AAs (60% vs 69%, P < 0.01). In multivariable modeling, adjusting for BP control significantly reduced the influence of race on graft loss . Thus, it is likely that improved BP control is necessary to improve graft outcome disparities for AAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a more recent analysis using national data, our research group demonstrated that posttransplant BP control (<140/90 mmHg) was significantly less common in AAs as compared with non‐AAs (60% vs 69%, P < 0.01). In multivariable modeling, adjusting for BP control significantly reduced the influence of race on graft loss . Thus, it is likely that improved BP control is necessary to improve graft outcome disparities for AAs.…”
Section: Discussionmentioning
confidence: 99%
“…The study was powered based on improving posttransplant hypertension control to goal levels. Grounded on preliminary data, we expected ~30% of kidney recipients to meet optimal hypertension goals (<130/80) . Using this as the baseline rate of control, this study had 80% power to detect an 18% improvement in rate of optimal BP control (30% baseline, 48% at the end of follow‐up).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…African Americans who do not carry these variants are assumed to carry the CYP3A5*1 allele and express high amounts of active CYP3A5 enzyme which confers a rapid metabolism phenotype, resulting in rapid tacrolimus clearance. African Americans, who more frequently carry a CYP3A5*1 allele and have higher risk of poorer outcomes, 30,31 may benefit most from genotype-directed dosing.…”
Section: Pharmacogenomics In Transplantationmentioning
confidence: 99%